Effect of Digital Wallet Usage on the Financial Behavior of Millennials in Metro Manila, Philippines - Mariniella B. Cagayao; Mia Lourdes R. Abergos; Maria Noraine Anciano; Cielo Mae Q. Del Rosario; Rhytheme A. Dionco; Jesus P. Briones (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
The widespread adoption of digital wallets in the Philippines has transformed how millennials manage their finances. This study examines the relationship between digital wallet usage and their financial behavior, focusing on spending habits, saving practices, and financial literacy. Employing a correlational descriptive design, data were collected from 401 millennials in selected cities within Metro Manila through a validated questionnaire distributed via Google Forms. Frequency, percentage, and mean were used to describe respondent profiles and usage patterns. In contrast, the Pearson correlation coefficient (r) was used to determine the strength and direction of the relationship between digital wallet usage and financial behavior. Findings revealed that digital wallets are deeply integrated into millennials’ daily financial activities, reflecting their reliance on digital platforms for convenience and accessibility. Regarding financial behavior, results indicated that millennials typically practice responsible financial management, including budgeting, saving, and tracking their expenses. Moreover, the results demonstrated a significant positive relationship between digital wallet usage and financial behavior, particularly in spending and saving habits. This finding suggests that responsible digital wallet usage enhances financial capability and strengthens users’ financial discipline and literacy. Furthermore, the study underscores the need for collaboration among financial technology firms, policymakers, and educators to integrate financial education into digital platforms and promote millennials’ financial well-being. A proposed action plan highlights partnerships through literacy initiatives, in-app learning, and incentive-based savings tools. The findings offer managerial insights for developing evidence-based strategies that enhance user engagement, encourage responsible financial behavior, and support financial well-being in the Philippines.